Local Health Department Accreditation Is Associated With Organizational Supports for Evidence-Based Decision Making - Peg Allen; Stephanie Mazzucca; Renee G. Parks; Mackenzie Robinson; Rachel G. Tabak; Ross Brownson; Ross Brownson; Ross Brownson (Frontiers Media S.A., 2019)
Introduction: Recent studies show that health department accreditation from the U.S. Public Health Accreditation Board (PHAB) drives performance management and quality improvement. PHAB standards call for agencies to use evidence in decision making. It is unknown whether accreditation is associated with organizational supports for evidence-based decision making (EBDM). Self-report data from a 2017 survey of U.S. local health departments were analyzed to test relationships of accreditation status with organizational supports for EBDM.Methods: A cross-sectional survey was conducted in this observational study. A total of 579 local health departments were invited to complete an online survey; 350 (60.4%) provided complete data for the present study. The dependent variables were six factors of organizational supports for EBDM previously validated through confirmatory factor analyses. Accreditation status (PHAB-accredited, preparing, not preparing) was the independent variable of interest. Logistic regression analyses controlled for governance (presence of a local board of health; state, local, or shared state and local governance) and jurisdiction population size.Results: PHAB-accredited health departments were more likely to report higher capacity for EBDM, resource availability for EBDM, and evaluation capacity than health departments that reported not yet preparing for accreditation. Health departments that reported preparing for PHAB accreditation showed a non-significant pattern of higher perceived supports for EBDM compared to departments not preparing for accreditation.Conclusion: PHAB standards and the accreditation process may help stimulate health department organizational supports for EBDM.